Implementation of good government governance, intellectual intelligence, emotional, and spiritual intelligence in managerial performance of village government management - Putri, I. G. A. M. Asri Dwija; Wirawati, Ni Gusti Putu (International research journal of management, IT and social sciences, 2020)
This research aims to describe the implementation of good government governance in Badung Regency Village Government, to examine the effect of good government governance, intellectual intelligence, emotional intelligence, and spiritual intelligence on the managerial performance of village government officials in Badung Regency. This research was conducted in Badung Regency with 230 respondents from the village government officials. Determination of the sample using non-probability sampling with a saturation sampling technique. Data collection methods were carried out using questionnaires and data analysis techniques using multiple linear regression analysis. The results of this research indicate that the variables of Good Governance, intellectual intelligence, emotional intelligence, and spiritual intelligence have a positive effect on the Managerial Performance of Village Government Officials in Badung Regency.